Artificial Intelligence dalam Layanan E-Konseling untuk Mendukung Mental Health Remaja: A Systematic Literature Review - Christina Ifanta Pratiwi; Dia Aubah Danila (Universitas Muhammadiyah Metro, 2026)
The development of digital technology has driven the integration of Artificial Intelligence (AI) into e-counseling services to support adolescent mental health. However, the effectiveness and challenges of AI implementation in this context have not yet been systematically mapped. This study aims to analyze the use of Artificial Intelligence in e-counseling services for adolescent mental health. This research employs a Systematic Literature Review (SLR) approach following the PRISMA guidelines. Article searches were conducted in the Google Scholar, ScienceDirect, Springer, PubMed, and ResearchGate databases. The findings indicate that AI-based chatbots, ChatGPT, and digital counseling platforms are capable of: (1) increasing the accessibility of counseling services, (2) providing initial psychological support, (3) assisting in the management of anxiety and stress, and (4) improving users' psychological well-being. AI is also considered to offer flexibility and comfort in the digital counseling process. Despite these benefits, the use of AI in e-counseling still faces challenges such as limited empathy, communication errors, AI hallucination, as well as ethical and data privacy issues. Therefore, AI should be positioned as a supporting tool for counseling services, not as a replacement for human counselors. Further research is needed to develop ethical protocols for AI use in adolescent counseling services.